Pengaruh Perlakuan Panas terhadap Kekerasan Baja Karbon Tinggi Bohler K460 - Asmeati Asmeati; Yanti Yanti (Politeknik Negeri Ujung Pandang, 2014)
Steel is the kind of metal that most widely used in various fields of engineering, particularly for industrial purposes, like building construction, aircraft construction, the manufacture of tooling equipment, and others. The number of usage on the kind metal is not separated from the properties owned, such as: easy to set up, but has strong and tough properties are easily processed by machining. The use of high-carbon steel is mainly used for making springs, and die cutting tools and forming tools. Carbon steel with high strength and hardness has a better after heat treatment. Heat treatment that frequently applied was the process of hardening (quench hardening) and tempering. This research would conducted in the laboratory experiments and is planned to last for 8 (eight) months. The material to be used was of high carbon steel. High carbon steel(Bohler K460) is heated to a temperature variation of 850oC, and 900oC with their respective holding time that used for 24 minutes, then quenched in the salt water. The research data was obtained through the process of tensile testing, hardness testing and metallographic structure. This research aims to determine the properties of hardness determine the effect of heat treatment parameters, namely temperature, holding time and cooling medium to high carbon steels violence at the time of quenching and to analyze the mechanical properties of high carbon steels as a result of variations in heat treatment. The results indicate that the variation of heat treatment parameters (i.e. temperature, holding time, and cooling media) against the carbon steel of high hardness makes a difference significant influence on the hardness after quenching process. With a temperature difference, 8500C and 9000C temperature and holding time for 24 minutes and then do the quenching process results in changes in the value of the highest hardness of 64.8 HRC was obtained after quenching process at a temperature of 900oC.